Bamboo leaf as quality fodder supplement for goat production in the dry semi-deciduous forest zone of Ghana - Daniel S Akoto; Samuel T Partey; Michael Mensah; Simon Abugre; Sellassie Akoto; Issah Seidu (Global Journal of Ecology - Peertechz Publications, 2022)
Limited access to fodder with fair nutritive characteristics especially during dry periods is a challenge to livestock farming. However, it is envisaged that evergreen bamboo with year-round litter production and high nutritive characteristics, may provide a valuable supplementary source of feed. In Ghana, bamboo use as fodder is largely unknown and efforts to promote its use will require an understanding of base feed quality and results disseminated. Therefore, a field fodder quality experimentation using twenty Djallonké kids (juvenile goats) of 1-year-old with a mean initial weight of 13.77 ± 1.16 kg for the trial and allotted to four dietary treatments in a completely randomized block design with five replicates per treatment was conducted. The study sought to assess the effect of leaves of two bamboo species (Oxytenanthera abyssinica and Bambusa balcooa) as a feed supplement to goats fed on basal diets of Pennisetum purpureum and Brachiaria decumbens. The fodder quality results indicated that nutrient composition and in vitro gas production of the treatments varied significantly among the grasses and the bamboo supplement. The highest crude protein and in vitro gas production was observed in O. abyssinica. Besides, O. abyssinica diets recorded the highest daily gain and the lowest feed-to-gain ratio. The treatment effect was significant on blood variables measured. Bamboo leaves are a viable feed supplement for goats as shown by their nutrient profile and positive influence on the growth performance of goats. Hence, the leaves of any of the bamboo species could be used as supplemental feed for goats.